BINOMIAL METHOD FOR PRICING PARISIAN AND PARASIAN OPTIONS - HAZNA LATIEFAH (10112003), EFA
Parisian and ParAsian options are becoming more popular, mainly due to the reduced cost to hold one of these options when compared to holding a standard option. Parisian and ParAsian options are path-dependent options whose payoff depend on time that the underlying assetÃ‚Â’s price has spent over a barrier. In the Parisian case, the time is counted consecutively. While, in the ParAsian case the time is counted cumulatively. This thesis proposes a binomial method to value Parisian and ParAsian options by considering all the possible paths that make the option actives. In order to obtain sufficiently precise estimates and to treat the near barrier problem in natural way, the writer used a binomial tree where the nodes of the tree are generated from the barrier. At last, this thesis provides a comparison of the result obtained by this method with finite difference method introduced by Haber and al.